Towards ensuring the realization of sustainable development goal 16 by governments in Nigeria: the role of the archives. Issue 1 (June 2020) - Anenene, Ese Eunice; Oyewole, Olawale
Abstract : Governments at all levels in Nigeria are striving to bring about peace, justice and good governance at a time when the country is being threatened by the challenges of insecurity and corruption. Such efforts by government mirrors the focus of Sustainable Development Goals (SDG) 16, which seeks to promote peaceful and inclusive societies for sustainable development and provide access to justice for all and build effective, accountable and inclusive institutions at all levels. In ensuring the realization of SDG 16, a strategic institution that could partner the government is the archives. This institution houses records/documents of permanent value that could be useful for problem solving and decision making. Records are the indispensable foundation of governance process because without reliable and authentic documentary evidence guiding all essential government process, governance, peace, justice and strong institutions cannot be achieved. This article highlights the factors hindering the realization of sustainable development goal 16 in Nigeria. The steps taken by government to address the factors are also examined and a case was made for the archives as an institution that should not be sidelined in the pursuit of good governance, peace and justice. The article explores the role of the archives in this regard and also provided practical recommendations to all stakeholders involved in the realization of SDG 16.